?DESCRIPTION OF A NEW SPECIES OF BLACKFL Y (DIPTERA: NEMATOCERA: SIMULIIDAE) FROM PAKIST AN - KHATOON, S.; HASAN, S.A. (Biological Sciences - PJSIR, 1995)
A new species Simulium (Wilhelmia) pindiensis was recorded from Potwar. This species was desribed in detail with special reference to the male and female genitalia. This species was also compared with the other known species of the genus.